2013
DOI: 10.3109/03091902.2013.779325
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probe to skin contact force on Cutometer MPA 580 measurements

Abstract: The purpose of this study is to test the hypothesis that increasing the force applied on the skin by the Cutometer MP580 probe will result in a decrease in the skin elasticity measures. Specifically, this study assessed the probe intrinsic weight plus the addition of a light mass (10 g and 20 g), a moderate mass (50 g and 100 g) and a high mass (200 g and 500 g) on skin elasticity measures. Primary outcome measures Uv, Ur, Uf, Ue and Ua, along with calculated measures Uv/Uf, Ua/Uf and Ur/Uf were assessed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 13 publications
1
44
0
1
Order By: Relevance
“…The dill treatment alone did not translate to a functional benefit, that is, increased elasticity based on Cutometer measurements (Fig 4a). Even though dill treatment in vitro resulted in an increase in elastin gene expression and cross-linking [15,37], in vivo this increase appeared to not be enough to translate to an increase in skin elasticity. An upregulation in the creation of elastic fibre elements, that is tropoelastin, might be needed for resultant impact in skin elasticity.…”
Section: Discussionmentioning
confidence: 90%
“…The dill treatment alone did not translate to a functional benefit, that is, increased elasticity based on Cutometer measurements (Fig 4a). Even though dill treatment in vitro resulted in an increase in elastin gene expression and cross-linking [15,37], in vivo this increase appeared to not be enough to translate to an increase in skin elasticity. An upregulation in the creation of elastic fibre elements, that is tropoelastin, might be needed for resultant impact in skin elasticity.…”
Section: Discussionmentioning
confidence: 90%
“…The skin contact portion of the probe contains a spring-mounted component that is designed to buffer small variations in force and thus prevent fluctuations in the force applied to the skin. 31 The probe is connected to the primary Cutometer hardware by a tube that transfers the suction generated by the primary hardware to the 4-mm probe opening. This suction then deforms the skin, pulling it into the probe.…”
Section: Instrumentationmentioning
confidence: 99%
“…collected data for all periods. 31 This investigator was masked to the results of the testing until all data collection was completed.…”
Section: Data Collectionmentioning
confidence: 99%
“…As noted by the company, individual technique, skin hydration level, humidity and temperature in the examination room, force applied [11] by the probe on the skin as well as the angle of the probe may all contribute to variability in measurements. Based on our clinical experience, the most significant of these relate to the multiple confounding factors associated with individual techniques of probe placement [11]. Excluding humidity and temperature, the vast majority of studies fail to specifically control and discuss a majority of these important factors when using the Cutometer [1,2,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 95%
“…Recently our team completed a prospective trial assessing the effect of mass loading on outcome measures [11]. The results of this study demonstrated a statistically and clinically significant alteration in all major outcome measures assessed by the Cutometer.…”
Section: Introductionmentioning
confidence: 97%